The Influence of Leadership Style, Awards, and Punishment on Praja Discipline at the Institute of Domestic Government (IPDN) Campus in West Sumatra - Jusmita Jusmita; Aldri Frinaldi (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
This article is about the influence of leadership style, reward and punishment on civil service discipline at Institute Of Domestic Government (Institut Pemerintahan Dalam Negeri/IPDN)  West Sumatra Campus. In addition, this article also discusses which variables have the most influence on civil service discipline. This research uses quantitative methods with explanatory quantitative research. The data collection technique used a questionnaire. The data analysis technique uses path analysis to see the causal relationship that begins with the classical assumption test and regression analysis with a Likert scale as the rating scale. The hypothesis will determine the contribution of the influence arising from one endogenous variable on an exogenous variable, either directly or indirectly. Overall, the results showed that leadership style had a positive and partial effect on reward, punishment and discipline. Rewards have a positive and partial effect on discipline. Punishment has a positive and partial effect on discipline. Leadership style through reward has an effect on discipline. Leadership style through punishment affects discipline. Leadership style, reward and punishment simultaneously influence discipline.